Phytochemical profiling and antimycobacterial activity of ethnomedically selected thottea species (aristolochiaceae) from peninsular Malaysia - Sabran, Siti Fatimah; Mohamed, Maryati; Abu Bakar, Mohd Fadzelly; Linatoc, Alona Cuevas (Medwell Journals, 2018)
This study was aimed to profile the major phytochemicals constituents and to evaluate the antimycobacterial activity of hexane, ethyl acetate, absolute methanol, water and 80% methanol root extracts of ethnomedically used plants Thottea grandiflora Rottb. and Thottea grandiflora T.L. Yao (Aristolochiaceae) from Johor, Peninsular Malaysia. The hexane, ethyl acetate, absolute methanol extracts of T. grandiflora and T. praetermissa were screened for major class of compounds using qualitative TLC fingerprinting while the water and 80% methanol extracts were profiled using GC-MS analysis to screen for major phytochemical constituents. By using Mycobacterium smegmatis as the model strain for TB, agar disk diffusion assay and Resazurin Microplate Assay (REMA) were employed to evaluate for their antimycobacterial activity in vitro. Further, the mechanism of action were described for growth curve, cellular leakage and scanning electron microscopy studies. TLC fingerprinting showed both species displayed a slight difference in phytochemical groups. By GC-MS analysis, acetic acid, n-hexadecanoic acid, glycerin and oleic acid were detected as among 11 major constituents in both species that might contribute to the antimycobacterial activity. Ethyl acetate extract of T. grandiflora displayed the largest inhibition zone at 100 mg/mL (14.92±0.86 mm) followed by ethyl acetate extract of T. praetermissa (12.08±2.15 mm). About 80% methanol and ethyl acetate extracts of T. grandiflora displayed the lowest minimum inhibition concentration (3.13 mg/mL) while 80% methanol extract of T. grandiflora displayed the lowest minimum mycobactericidal concentration (3.13 mg/mL), followed by 80% methanol and ethyl acetate extracts of T. praetermissa (6.25 mg/mL). Growth curve analysis showed that at 2-fold of MIC, 80% methanol extract of T. grandiflora successfully inhibited the bacterial cell growth within 8 h of treatment by causing significant cellular leakage and severe damage to the cells. The results scientifically validated the plants used in Jakun’s traditional medicine displayed promising antimycobacterial properties and further studies would lead to the discovery of novel biomarker in Thottea species.